A new SDN-based load balancing algorithm for IoT devices - Hind Sounni; Najib El kamoun; Fatima Lakrami (Institute of Advanced Engineering and Science, 2021)
Nowadays, the emergence of the Internet of things devices has wholly revolutionized the customer's communication habits. The information can be collected at any time and anywhere. However, the mobility of communication devices in a dense network results inseveral problems, such as unbalanced network load and increased bandwidth demands, which decrease the network performance. To deal with these issues, this paper proposes a new load balancing algorithm based on the software-defined Network to enhance the performance of mobile devices communication over a Wi-Fi network. The use of the software-defined network automatizes the configuration of the network through a centralized controller; it provides programmability and an overall view of the network, along with optimizing resource allocation based on real-time network information, which facilitates the implementation of our algorithm. The proposed algorithm is implemented and evaluated through simulation using mininet-WiFi. The results indicate that our proposed method provides an efficient network load balancing and improves performancdevices' performance.